IMPLEMENTASI MUSAQAH DALAM PRAKTEK PENGELOLAAN KEBUN KELAPA SAWIT DI DESA KOREK SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Ubay Dillah; Moch Fahmi Riza; Ishar Pulungan (Al-Aqad, 2024)
The purpose of this research is to find out: 1) whether Oil palm plantation management agreements between land owners and land managers in Korek Village; 2) Does the oil palm plantation management agreement in Korek Village fulfil the musaqah provisions in KHES. The data collection method in this research is field or empirical research, this research data collection technique uses observation, interviews and documentation techniques. Data analysis was carried out descriptively through four stages, namely: data collection, data reduction, data presentation and drawing conclusions. The results show that: 1) Regarding capital, the practice of musaqah is carried out by land owners with land managers, the land owner hands over oil palm plants (capital) and the land manager is responsible for the capital handed over by the land owner. The distribution of profits from the musaqah contract practice is expressed verbally, namely by sharing profits of 30% and 70% where the land manager gets 30% while the land owner gets 70% and some share the profits at 40% and 60% of the profits obtained from the musaqah contract practice. the. Based on the data in this research, the working time carried out by the parties varies, some parties determine the working time once every two years by starting a new contract, while others do not use a time limit. 1) Not all articles contained in the Compilation of Sharia Economic Law are applied in the musaqah contract, especially those contained in Article 266 concerning the pillars of musaqah, but there are most of the articles that have been implemented in the practice of managing oil palm plantations in Korek Village, Sungai Ambawang District, Kubu Raya Regency.